2019
DOI: 10.1097/jnr.0000000000000307
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Critical Thinking Skills and Learning Styles and Academic Achievement of Nursing Students

Abstract: Background: Academic achievement is one of the most important indicators in evaluating education. Various factors are known to affect the academic achievement of students. Purpose: This study was performed to assess the relationship between critical thinking skills and learning styles and the academic achievement of nursing students. Methods: In this cross-sectional study, 139 sophomores to senior-year nursing students were selected using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
3
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 11 publications
5
65
3
8
Order By: Relevance
“…The researchers recommend studying other variables such as motivation, learning habits, school environment. However, this research is in contradiction with a survey (Shirazi & Heidari, 2019) which proved that there was a relation between learning styles and academic achievement among university students. Unconsciously, a teacher can support a single learning style that is not appropriate in relation to the subject and the content of education (Pasiar et al, 2015).…”
Section: Introductioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The researchers recommend studying other variables such as motivation, learning habits, school environment. However, this research is in contradiction with a survey (Shirazi & Heidari, 2019) which proved that there was a relation between learning styles and academic achievement among university students. Unconsciously, a teacher can support a single learning style that is not appropriate in relation to the subject and the content of education (Pasiar et al, 2015).…”
Section: Introductioncontrasting
confidence: 98%
“…This factor changes the form or method of teaching and therefore is more based on experiential learning. This type of education is also beneficial for the students themselves (Pratama, 2015) and contributes to strengthening students' abilities to improve their academic performance (Espinoza-Poves et al, 2019;Shirazi & Heidari, 2019). Smith and Emerson (2017) research, which confirmed that academia is primarily focused on academic research but lacks significant practical experience or academic certification, can be used to explain why this is the case.…”
Section: Introductionmentioning
confidence: 95%
“…Considering the importance of critical thinking skills in nursing, it is inevitable to use OSCE since it encourages critical thinking in nursing students [32]. Since OSCE is a formal practical examination, it is natural to anticipate high levels of anxiety among students taking the test.…”
Section: Discussionmentioning
confidence: 99%
“…This initiative was designed to increase student engagement and improve the quality of education through the use of ICT. Through the use of this virtual learning environment, we focus on facilitating the acquisition of critical thinking skills through reflection on how the ways in which evidence is produced necessitate both continuous training and a critical attitude toward this evidence (Lee, Abdullah, Subramanian, Bachmann, & Ong, 2017;Reed & Edmunds, 2015;Schuelke & Barnason, 2017;Shirazi & Heidari, 2019).…”
Section: Objectivesmentioning
confidence: 99%